2020
DOI: 10.3389/fchem.2020.00306
|View full text |Cite
|
Sign up to set email alerts
|

Simple Perylene Diimide Cyclohexane Derivative With Combined CPL and TPA Properties

Abstract: In this work we describe the linear and non-linear (chiro)optical properties of an enantiopure bis-perylenediimide (PDI) cyclohexane derivative. This compound exhibits upconversion based on a two-photon absorption (TPA) process with a cross-section value of 70 GM together with emission of circularly polarized luminescence (CPL), showing a g lum in the range of 10 −3 . This simple structure represents one of the scarce examples of purely organic compounds combining both TPA and CPL responses, together with larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
4
11
0
Order By: Relevance
“…The g lum values of around 1 ⋅ 10 −3 for the heavily twisted molecules are of typical magnitude and are comparable to those of chiral peropyrene reported by Chalifoux et al . and other chiral organic molecules [37,50–53] . The monosignated spectra of the two respective P ‐/ M ‐enantiomers are again mirror images, and the observed Stokes shifts are in accordance with the Stokes shifts obtained by UV/Vis/NIR and fluorescence measurements.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The g lum values of around 1 ⋅ 10 −3 for the heavily twisted molecules are of typical magnitude and are comparable to those of chiral peropyrene reported by Chalifoux et al . and other chiral organic molecules [37,50–53] . The monosignated spectra of the two respective P ‐/ M ‐enantiomers are again mirror images, and the observed Stokes shifts are in accordance with the Stokes shifts obtained by UV/Vis/NIR and fluorescence measurements.…”
Section: Resultssupporting
confidence: 84%
“…and other chiral organic molecules. [ 37 , 50 , 51 , 52 , 53 ] The monosignated spectra of the two respective P ‐/ M ‐enantiomers are again mirror images, and the observed Stokes shifts are in accordance with the Stokes shifts obtained by UV/Vis/NIR and fluorescence measurements. The sign of the CPL spectrum matches the sign of the longest wavelength transition in the CD spectrum.…”
Section: Resultssupporting
confidence: 79%
“…Corresponding parameters including TPA cross-section and the power-dependent luminescence curves have been measured to exhibit TPA process, with intensity being proportional to the square of the excitation light intensity. Currently, direct measuring CPL based on TPA-UC gives the rare case, although some studies have reported several kinds of systems which can exhibit both CPL and TPA-UC [272][273][274][275]. Exploration of more systems and corresponding mechanism should be necessary for the improvement of CPL based on TPA-UC.…”
Section: Photon Upconversion Systemsmentioning
confidence: 99%
“…Absorption spectra of the self-assemblies in chloroform/MCH solutions are also similar for ( S )-Binaph-PDI and Biph-PDI ( Figure 2A ), that are typical for aggregates composed of PDI units with suppressed absorptivity ( Reine et al, 2020 ). The absorption band at 550 nm typical for the homochiral assembly of Binaph-PDI ( Kumar et al, 2014 ) slightly shifted to 547 nm for the self-assembly of Biph-PDI together with a slight appearance of a shoulder at 565 nm, which was absent for ( S )-Binaph-PDI.…”
Section: Resultsmentioning
confidence: 77%